Strength training (IAAF @-Letter for CECS Level II Coaches, 2003)
The motor characteristic `strength` is made up of the individual components starting strength, explosive strength, maximal strength, speed strength and strength endurance. Starting, explosive and maximal strength form the basis for speed strength and together with fatigue resistance influence the development of strength endurance. Among the action forms of the muscles a distinction is made between isometric (static), concentric (contracting/ overcoming) and eccentric (lengthening/yielding) forms of action as well as the combination of eccentric- concentric movements, the stretch-shortening cycle (SSC).